2011
DOI: 10.1016/j.archoralbio.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

New antimicrobial therapies used against fungi present in subgingival sites—A brief review

Abstract: Although the main reservoir of Candida spp. is believed to be the buccal mucosa, these microorganisms can coaggregate with bacteria in subgingival biofilm and adhere to epithelial cells. The treatment of periodontal disease includes scaling and root planning (SRP) associated with proper oral hygiene. However, some patients may have negative responses to different therapeutic procedures, with a continuous loss of insertion, so the use of antimicrobials is needed as an adjuvant to SRP treatment. The use of a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 89 publications
(124 reference statements)
0
44
0
Order By: Relevance
“…As in the vast majority of microbial biofilms (Rajendran et al, 2010), sessile cells within C. albicans biofilms are less susceptible to antimicrobial agents than are planktonic cells (Kuhn & Ghannoum, 2004). The progression of drug resistance within Candida biofilms has been associated with a parallel increase in the maturation process (Sardi et al, 2011). Furthermore, some studies have also shown that biofilms of Candida develop statically in the presence of a minimal matrix and exhibit the same level of resistance to drugs (fluconazole and amphotericin B) as cells grown in a shaker and exhibiting large amounts of matrix (Seneviratne et al, 2008;Sardi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the vast majority of microbial biofilms (Rajendran et al, 2010), sessile cells within C. albicans biofilms are less susceptible to antimicrobial agents than are planktonic cells (Kuhn & Ghannoum, 2004). The progression of drug resistance within Candida biofilms has been associated with a parallel increase in the maturation process (Sardi et al, 2011). Furthermore, some studies have also shown that biofilms of Candida develop statically in the presence of a minimal matrix and exhibit the same level of resistance to drugs (fluconazole and amphotericin B) as cells grown in a shaker and exhibiting large amounts of matrix (Seneviratne et al, 2008;Sardi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The progression of drug resistance within Candida biofilms has been associated with a parallel increase in the maturation process (Sardi et al, 2011). Furthermore, some studies have also shown that biofilms of Candida develop statically in the presence of a minimal matrix and exhibit the same level of resistance to drugs (fluconazole and amphotericin B) as cells grown in a shaker and exhibiting large amounts of matrix (Seneviratne et al, 2008;Sardi et al, 2011). The increase in resistant strains necessitates a search for new targets for new antifungal agents (J. M. Sardi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In normal healthy gingivae, the free gingival margin and the tooth surface are in close proximity to each other, leaving very little space for microbial colonization (13). Periodontitis is an infection of the oral gingival tissue that is caused by a combination of microorganisms commonly found in dental plaque, such as streptococci, staphylococci, fusobacteria, Porphyromonas species, Campylobacter species, actinobacteria, and many others (30,37). As periodontitis manifests, the gingival margin becomes enlarged, causing the gingival tissue to detach from the tooth, resulting in the formation of periodontal pockets.…”
mentioning
confidence: 99%
“…Candida species have been isolated from 40 to 60% of healthy mouths (29), although they are rarely found in subgingival sites in patients with good oral health (35). Candida species have frequently been isolated from periodontal pockets; however, their role, if any, in the etiology of periodontitis remains to be elucidated (5,8,27,30,35,37). Several previous studies investigated the prevalence and possible role of Candida species in periodontitis, all of which identified C. albicans as the Candida species most frequently isolated from periodontal pockets (3,9,19,20,31,35).…”
mentioning
confidence: 99%
“…Plants are good options for obtaining a wide variety of drugs [5,6] (Table 1). Another promising antifungal strategies are Silver nano particles (interfere with microbial DNA replication within bacteria and fungi), Anti-Candida antibodies (can reduce the binding of Candida to various surfaces), Photodynamic therapy (inactivation of the fungus) and Gold nano particle conjugate (mediated photodynamic therapy may be used against nosocomially acquired refractory C albicansbiofilms) [7][8][9][10].…”
Section: Candida Biofilm and New Antifungal Strategiesmentioning
confidence: 99%